Static and dynamic behavior of loose sand and silty sand treated with guar and agar gums (Micro and macro study) - Parviz Maleki; Mehdi Gharib; Saman Soleimani Kutanaei; Hossein Ghasemnejad; Nima Ranjbar Malidarreh (Carbohydrate Polymer Technologies and Applications, 2025)
This study evaluates the impact of guar gum and agar gum on the enhancement of mechanical, shear, and liquefaction resistance properties of loose sand and silty sand. Various tests, including indirect tensile strength (ITS), unconfined compressive strength (UCS), unconsolidated undrained triaxial (UU), direct shear test (DST), ultrasonic pulse velocity (UPV), scanning electron microscopy (SEM) and consolidated undrained cyclic triaxial (CCU), were conducted on sand soil and silty sand treated with various contents (0.5 %, 1 %, and 2 % by dry weight of soil) of agar gum and guar gum. The results showed a significant increase in strength with biopolymer stabilization. The UCS of untreated soils showed negligible resistance (UCS≈0 kPa), while treated with 2 % agar and guar gum, the UCS reached 2322 and 1911 kPa in sandy soil, and 3189 and 2522 kPa in silty sand, respectively. In contrast, increasing the biopolymer content led to a decrease in the drained internal friction angle. The liquefaction resistance of sand and silty sand was substantially improved with agar gum stabilization. At a cyclic stress ratio (CSR) of 0.2, stabilization with 2 % agar gum increased the number of cycles to liquefaction (NL) in sandy soil by 440 %.